Reversing Pdgfrβ signaling restores metabolically active beige adipocytes by alleviating ILC2 suppression in aged and obese mice - Abigail M. Benvie; Daniel C. Berry (Elsevier, 2024)
Objective: Platelet Derived Growth Factor Receptor Beta (Pdgfrβ) suppresses the formation of cold temperature-induced beige adipocytes in aged mammals. We aimed to determine if deleting Pdgfrβ in aged mice could rejuvenate metabolically active beige adipocytes by activating group 2 innate lymphoid cells (ILC2), and whether this effect could counteract diet-induced obesity-associated beige fat decline. Methods: We employed Pdgfrβ gain-of-function and loss-of-function mouse models targeting beige adipocyte progenitor cells (APCs). Our approach included cold exposure, metabolic cage analysis, and age and diet-induced obesity models to examine beige fat development and metabolic function under varied Pdgfrβ activity. Results: Acute cold exposure alone enhanced metabolic benefits in aged mice, irrespective of beige fat generation. However, Pdgfrβ deletion in aged mice reestablished the formation of metabolically functional beige adipocytes, enhancing metabolism. Conversely, constitutive Pdgfrβ activation in young mice stymied beige fat development. Mechanistically, Pdgfrβ deletion upregulated IL-33, promoting ILC2 recruitment and activation, whereas Pdgfrβ activation reduced IL-33 levels and suppressed ILC2 activity. Notably, diet-induced obesity markedly increased Pdgfrβ expression and Stat1 signaling, which inhibited IL-33 induction and ILC2 activation. Genetic deletion of Pdgfrβ restored beige fat formation in obese mice, improving whole-body metabolism. Conclusions: This study reveals that cold temperature exposure alone can trigger metabolic activation in aged mammals. However, reversing Pdgfrβ signaling in aged and obese mice not only restores beige fat formation but also renews metabolic function and enhances the immunological environment of white adipose tissue (WAT). These findings highlight Pdgfrβ as a crucial target for therapeutic strategies aimed at combating age- and obesity-related metabolic decline.